Caracterização, criopreservação e diferenciação in vitro de células tronco, derivadas de amniótica e gelatina de Wharton canina, visando a formação de um banco de células tronco - Arruda, Isadora [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Mesenchymal stem cells (MSCs) are present in most of adult tissues, and are therefore attractive for cell therapy. Because of their high potential for differentiation and proliferation, they are being used in tissue reconstruction. This experiment aimed to enrich knowledge of canine MSCs derived from umbilical cord and amniotic membrane before and after cryopreservation regarding the formation of a cell bank. Thus, eight samples of amniotic membrane and eight samples of Wharton’s jelly were obtained from dogs at birth, which were subjected to enzymatic digestion and basal medium culture. Slow freezing of a sample from each culture was held at the first passage and stored for four weeks. Before and after freezing cells were subjected to characterization being observed adhesion, proliferation, differentiation and expression of surfaces markers using flow cytometry and immunocytochemistry. Based on these analyses it was demonstrated that the cells before and after cryopreservation exhibited similar behavior for proliferation and cell growth. Cell viability of amniotic membrane showed 97.0% of viable cells before freezing and 94.6% after, and the Wharton’s jelly 98.8% before and 93.5% after cryopreservation. The potential of the osteogenic and adipogênica differentiation as well as maintained, however it required a longer time (p <0.05) for the cells from Wharton's jelly to differentiate themselves after freezing. And still maintained the expression of CD44, at satisfactory levels to be considered positive, where the amniotic membrane expressed 85.6% before and 67.8% after freezing and Wharton’s Jelly expressed 86.0% before and 82.1% after cryopreservation and absence of expression of CD34 and MHC II. A peculiar feature observed was that before and after freezing spontaneous differentiation in both lineages (osteogenic and adipogenic) occurred in the controls that were not induced to differentiation. We conclude that ...

As células tronco mesenquimais (CTMs) estão presentes na maioria dos tecidos adultos, e por isso são atrativas para a terapia celular, pois possuem alto potencial de diferenciação e proliferação, sendo assim, utilizadas na reconstrução tecidual. O presente experimento objetivou obter maior conhecimento sobre CTMs derivadas da membrana amniótica e cordão umbilical de cães, antes e após criopreservação, visando a formação de um banco de células. Assim, oito amostras de membrana amniótica e oito amostras de gelatina de Wharton foram obtidas de cesarianas, as quais foram submetidas a digestão enzimática, e cultivadas em meio basal. Uma porção celular, de cada amostra, foi criopreservada em 1ª passagem, de forma lenta, e armazenada por 4 semanas. As células antes e após a criopreservação foram submetidas à caracterização, onde foi observado características de adesão, proliferação, diferenciação e expressão de marcadores de superfícies utilizando-se citometria de fluxo, e imunocitoquímica. A partir destas avaliações, foi possível demonstrar que as células antes e após a criopreservação exibiram comportamento semelhante, quanto à proliferação e crescimento. A viabilidade celular da membrana amniótica apresentou 97,0% das células viáveis antes da criopreservação e 94,6% após, já a gelatina de Wharton 98,8 antes e 93,5% após a criopreservação. O potencial de diferenciação nas linhagens osteogênica e adipogênica foi mantido, no entanto foi necessário um tempo maior (p<0,05) para que as células de gelatina de Wharton se diferenciassem após a criopreservação. E ainda mantiveram a expressão de CD44, em níveis satisfatórios para que fossem consideradas positivas, onde a membrana amniótica expressou 85,6% antes e 67,8% após a criopreservação e a gelatina de Wharton expressou 86,0% antes e 82,1% após a criopreservação e a ausência de expressão ...
Keywords: Cão - Reprodução; Células-Tronco - Criopreservação; Reprodução animal; Cordão umbilical; Âmnio; Geleia de Wharton; Stem cells